ACLC Inc.: Snuggle hoodie: The perfect blend to your hoodies and blankets - Tan, Chelsea Lynn Young (Animo Repository, 2021)
Snuggle Hoodie is a jacket that is a jacket-blanket hybrid with features such as reversibility and multiple pockets. The idea came to mind to have a snuggle experience during a binge watch and cold weather. The oversize feature, the bright color variations, and the soft fleece makes it a wonderful product to relax with.